Management of cardiovascular risk factors in patients with ANCA‐associated vasculitis. Issue 4 (16th February 2017) - Bramlage, Carsten Paul; Kröplin, Juliane; Wallbach, Manuel; Minguet, Joan; Smith, Katherine Helen; Lüders, Stephan; Schrader, Joachim; Patschan, Susan; Gross, Oliver; Deutsch, Cornelia; Bramlage, Peter; Müller, Gerhard Anton; et al.
Abstract: Objectives: Anti‐neutrophil cytoplasmic antibody (ANCA)‐associated vasculitis (AAV) is accompanied by increased cardiovascular (CV) risk. Treatment of AAV patients includes the management of conventional CV risk factors, primarily hypertension and hypercholesterolemia, while lipoprotein(a) (LP(a)) is an emerging potential target. Methods: We performed a multicenter, retrospective study in Germany. Patients were considered if they were between 18 and 90 years old and presented with AAV. Patients with arterial hypertension but no autoimmune disease were used as a control group (HTN reference group). Results: Compared to the reference group (n = 52), CV disease burden was significantly greater in patients with AAV (n = 53). Hypercholesterolemia was also more common in the AAV patients (71.7% vs 46.2% for the HTN; P  = .008). Lipoprotein(a) levels were elevated in both groups, with 11.3% and 17.3% of the AAV and HTN groups, respectively, displaying a level above 0.6 g/l ( P  = .083). Guideline‐recommended targets for low‐density lipoprotein cholesterol and blood pressure levels were rarely met. According to Kidney Disease: Improving Global Outcomes guidelines, 72.5% of the patients with AAV should have been taking statins and/or ezetimibe for treatment of hyperlipidemia; however, only 24.3% of them were receiving such treatment. Blood pressure below ≤140/90 mmHg was reached in 78.6% of the patients with chronic kidney disease. However, for patients with chronic kidney disease and an albumin excretion rate of >30 mg/day, the recommended blood pressure is ≤130/80 mmHg, a value that was not reached in 65% of the AAV patients. Conclusion: Patients with AAV are at high CV risk, but management of the associated risk factors is poor. In addition to improving the treatment of hypercholesterolemia and hypertension, lipoprotein(a) is a further potential target for reducing CV risk in individuals with AAV.